2017
DOI: 10.1038/s41598-017-03565-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of transient high temperature treatment on the intestinal flora of the silkworm Bombyx mori

Abstract: The silkworm Bombyx mori is a poikilotherm and is therefore sensitive to various climatic conditions. The influence of temperature on the intestinal flora and the relationship between the intestinal flora and gene expression in the silkworm remain unknown. In the present study, changes of the intestinal flora at 48, 96 and 144 h following transient high temperature treatment (THTT) of 37 °C for 8 h were investigated. According to principal component analysis, the abundances of Enterococcus and Staphylococcus s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 47 publications
3
12
2
Order By: Relevance
“…Furthermore, we investigated the specific taxa in duodenal, jejunal, and ileal microbiota that were significantly associated with high temperature, which allowed us to determine whether high ambient temperature could change the intestinal microbial community and functions. The present study indicated that abundance of Enterococcus decreased after the ducks were exposed to high temperature, suggesting that the abundance of Enterococcus in the gut contents was significantly affected and sensitive to high temperature, which is consistent with previous results in silkworms ( Sun et al., 2017 ). Enterococcus is characterized by its prebiotic properties in the intestine, which has been reported to have beneficial effects on enhancing the intestinal barrier function ( Pedicord et al., 2016 , Huang et al., 2019 ).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, we investigated the specific taxa in duodenal, jejunal, and ileal microbiota that were significantly associated with high temperature, which allowed us to determine whether high ambient temperature could change the intestinal microbial community and functions. The present study indicated that abundance of Enterococcus decreased after the ducks were exposed to high temperature, suggesting that the abundance of Enterococcus in the gut contents was significantly affected and sensitive to high temperature, which is consistent with previous results in silkworms ( Sun et al., 2017 ). Enterococcus is characterized by its prebiotic properties in the intestine, which has been reported to have beneficial effects on enhancing the intestinal barrier function ( Pedicord et al., 2016 , Huang et al., 2019 ).…”
Section: Discussionsupporting
confidence: 93%
“…Dominant gut bacteria found in this study, such as Enterobacter , Acinetobacter , Methylobacterium , Wolbachia and Streptococcus , are common in other lepidopteran insects . There were, however, also potentially pathogenic species, especially associated with A. major and E. similis .…”
Section: Discussionmentioning
confidence: 56%
“…Dominant gut bacteria found in this study, such as Enterobacter, Acinetobacter, Methylobacterium, Wolbachia and Streptococcus, are common in other lepidopteran insects. [64][65][66] There were, however, also potentially pathogenic species, especially associated with A. major and E. similis. Recent advances in studying insect-microbe interactions have shown that entomopathogens play an important role in insect pest biocontrol.…”
Section: Discussionmentioning
confidence: 99%
“…In yeast, increased total CL levels were found under temperature stress (Luévano-Martínez et al, 2015 ). A recent study observed increased total levels of CL and increased linoleic acid (18:2) content in CL, in skeletal muscle in response to overload stimuli (Fajardo et al, 2017 ).…”
Section: Is Essential For Mitochondrial Functionsmentioning
confidence: 99%